Seasonal Variation in Undiagnosed HIV Infection on the General Medicine and Trauma Services of Two Urban Hospitals - Brady, Kathleen A (Blackwell Science Inc, 2005)
OBJECTIVE: To examine the seroprevalence of undiagnosed HIV and variation by season among patients admitted to the general internal medicine (GIM) and trauma services of two urban hospitals. DESIGN: A cross-sectional blinded HIV-1 seroprevalence survey. SETTING: A 725-bed academic medical center's hospital and an affiliated 324-bed tertiary care hospital. PARTICIPANTS: Residual serological specimens were obtained for unique patients aged 17 to 65 to study services in summer (June 16 to September 4, 2001) and fall to winter (November 1, 2001 to January 8, 2002). METHODS: Hospital files provided data on demographics, service type, and discharge clinical categories (fall–winter group only). HIV ELISA (enzyme-linked immunosorbent assay) tests with confirmatory Western blot were linked to subjects' de-identified files. We excluded 34 subjects with known HIV. Of the remaining unique admissions in summer (n=604) and fall–winter (n=978), 60% and 55% were tested, respectively. Predictors of undiagnosed HIV infection were examined using multivariate analysis. RESULTS: The summer cohort (n=362) had significantly lower unadjusted seroprevalence of undiagnosed HIV infection (1.4%; 95% confidence interval [CI], 0.4% to 3.2%) than the fall–winter cohort (n=539; 3.7%; 95% CI, 2.3% to 5.7%; P=.04). Overall, undiagnosed HIV was somewhat less likely in women (adjusted odds ratio [AOR], 0.45; 95% CI, 0.19 to 1.07) but more likely in black patients (AOR, 3.46; 95% CI, 0.70 to 17.06). In the fall–winter cohort, undiagnosed HIV was more likely for discharges with the following clinical categories versus those with a cardiac condition: dermatologic/breast (AOR, 14.90; 95% CI, 1.20 to 184.77), renal/urological (AOR, 22.43; 95% CI, 2.12 to 236.75), or infectious (AOR, 31.08; 95% CI, 2.40 to 402.98). CONCLUSIONS: The higher seroprevalence of undiagnosed HIV in the fall–winter admissions to GIM and trauma services supports especially targeting HIV testing in these months.